Classification and Mathematical Expression of Different Interference Signals on a GPS Receiver. Issue 1 (March 2015) - Bek, Mohammad K.; Shaheen, Ehab M.; Elgamel, Sherif A.
Abstract Interference is one of the major concerns in using the global positioning system (GPS) for civilian and military applications. In this paper, a new classification of different interference signals is presented. This classification is based on the interference signal's bandwidth and the GPS correlator coherent integration time. The new classification simplifies the evaluation of the interference effect on the GPS receiver correlator output for different interference signals such as: continuous wave interference (CWI), narrowband interference (NBI), partial band interference (PBI), and broadband interference (BBI). Novel closed form analytical expressions for the GPS receiver correlator output power for CWI, NBI, PBI, and BBI are derived. The effect of the GPS correlator coherent integration time, the interference bandwidth, and the interference frequency error are also investigated under the impact of these types of interference. Copyright © 2015 Institute of Navigation.